Synthesis of Bis-Isoxazolines - Gajbhiye, J.M.; Jamode, V.S. (Asian Journal of Chemistry, 2010)
Bis-isoxazolines (II) have been synthesised by the condensation of bis-chalcones (I) with hydroxylamine hydrochloride in pyridine medium. Structures of these compounds have been established by chemical properties, elemental analysis and spectral analysis (viz., IR and NMR).